NUTRITION-BASED EDUCATION TO PREVENT ANEMIA: THE EFFECT OF PSIDIUM GUAJAVA L. AND PHOENIX DACTYLIFERA PUDDING ON HEMOGLOBIN LEVELS AMONG ADOLESCENT - Adelia Dwi Iriyanti; Reny Retnaningsih (CV. TOTUS TUUS, 2025)
Iron-deficiency anemia remains a critical public health issue among adolescent girls, particularly in rural areas with limited access to nutrition education and supplementation. Red guava (Psidium guajava L.) and dates (Phoenix dactylifera) are known to contain vitamin C and iron, respectively, which are essential for hemoglobin synthesis. This study aims to evaluate the effect of consuming pudding made from red guava and dates on hemoglobin (Hb) levels in female adolescents with anemia in Lebakadi Village, Lamongan Regency. A quasi-experimental non-equivalent control group design was used involving 60 adolescent girls aged 14–17 years. Participants were divided into an intervention group (n=30) receiving 100g/day of guava-date pudding for 14 days and a comparison group (n=30) receiving placebo pudding. Hb levels were measured pre- and post-intervention using a digital hemoglobinometer. Data were analyzed with paired and independent sample t-tests (p<0.05). The treatment group showed a significant increase in mean Hb levels from 10.43±0.31 g/dL to 12.00±0.55 g/dL (p=0.000), while the comparison group showed no significant change (11.45±0.25 g/dL to 11.47±0.27 g/dL, p=0.229). No adverse effects were reported. Guava-date pudding significantly improves Hb levels in anemic adolescent girls. This intervention is culturally appropriate, well-accepted, and effective as a non-pharmacological strategy. The findings support the implementation of food-based anemia prevention programs in schools and rural health posts. Future research should involve a larger, more diverse sample and include additional biomarkers such as ferritin and TIBC.